An outbreak of severe infectious diseases caused by methicillin-resistant Staphylococcus aureus USA300 clone among hospitalized patients and nursing staff in a tertiary care university hospital. Issue 1 (January 2020) - Kobayashi, Takehito; Nakaminami, Hidemasa; Ohtani, Hiroshi; Yamada, Kanako; Nasu, Yutaka; Takadama, Shunsuke; Noguchi, Norihisa; Fujii, Takeshi; Matsumoto, Tetsuya
Abstract: The USA300 clone, which produces Panton-Valentine leukocidin (PVL), is a major highly pathogenic community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) clone that is spreading throughout the world. Although the prevalence of the USA300 clone in Japan was very limited a decade ago, its incidence has been increasing in both community and hospital settings in recent years. There is great concern that the USA300 clone will cause more complicated diseases and become a serious threat to immunocompromised patients in hospital settings. Here, we report an outbreak of severe infectious diseases in a tertiary care university hospital involving the incidence of deep infections, including bacteremia, and continuous and frequent isolation of MRSA strains for five months from six patients and a healthy nursing staff member in the same ward. The genotype of all MRSA isolates was identical to that of the USA300 clone. Furthermore, pulsed-field gel electrophoresis analysis indicated that all MRSA had the same patterns. These data demonstrate that a USA300 clone outbreak had occurred in the hospital. Fortunately, this outbreak was terminated subsequent to the interventions of the infection control team and all patients recovered following the appropriate therapies. Our report demonstrates that patients carrying highly pathogenic CA-MRSA have the potential to become a source of nosocomial outbreaks that can spread to healthy healthcare workers. Therefore, stricter standard precautions should be applied for all patients at the time of admission to prevent such nosocomial outbreaks.